ANALISIS PERBANDINGAN 4 MAZHAB TENTANG PERNIKAHAN DALAM ISLAM - Umi Hani (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2019)
This study aims to analyze: 1) the Islamic view of the  marriages, 2) a comparison of 4 schools about the marriages of marriage in Islam. Type of juridical-normative research or doctrinal legal research. Library research, namely research activities carried out by collecting and tracing data and processing (books, literature and library materials) related to the topic of discussion. The type of research is qualitative research which is a particular tradition in social science that is fundamentally dependent on humans in its own region and relates to these people in its discussion and in its terminology. Material of the Law of the Qur'an, hadith, and the opinion of the school of Iman Syafii, Hanafi Faith, Maliki Imam, Hambali Faith. The data analysis method used in this research is analytical descriptive method.The results of the study explain that dowry may be in the form of money, jewelry, household furniture, animals, services, commercial property or other objects that have a price. or a sack of wheat. If it is not known from various aspects that allow determination of the amount of dowry, then according to all schools except Maliki, the contract remains valid, but the dowry is null. While Maliki believes that the contract is invalid and in fact before mixing at the campuri, the contract is declared valid by using mahar mitsli. Maliki said that if the contract had not been mixed it was invalid. But if there had been a mixture then the contract was declared valid and the wife had the right to mitsli mahr. Meanwhile, Syafi'i, Hanafi and Hambali argue that, the contract remains valid, and the wife has the right to mitsli mahr.